(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
Radiotherapy is one of the most common and effective cancer treatments. However, it has a profound impact on ovarian function, leading to premature ovarian failure. With the hope of preserving fertility in cancer survivors, the need for an effective radioprotective therapy is evident. The present study investigated the mechanism of potential radioprotective effect of cetrorelix on radiation-induced ovarian failure and whether cetrorelix can stimulate in vivo follicular development in experimental rats. Immature female rats were either exposed to gamma radiation (3.2 Gy, LD20), once and/or treated with cetrorelix (0.5 mg/kg), once daily for 10 days before irradiation. Histopathological examination further confirmed the radioprotective efficacy of cetrorelix and its in-vivo effect on ovarian follicles’ maturation .Cetrorelix significantly reversed the oxidative stress effects of radiation that was evidenced by increasing in lipid peroxide level and decreasing in glutathione level. In conclusion, cetrorelix showed a radioprotective effect.